2019
DOI: 10.3126/jbssr.v4i2.29481
|View full text |Cite
|
Sign up to set email alerts
|

Human Resource Development and Employee Engagement in Nepalese Commercial Banks

Abstract: The objective of the present study is to analyse the impact of human resource development on employee engagement in Nepalese commercial banks by taking three human resource development components of training and development, career development and performance management as independent variables, and employee engagement as a dependent variable. Using the random sampling, 384 employees were selected, and a questionnaire survey was carried out to collect data. Using F-test and t-test, the study found that the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 9 publications
0
19
2
Order By: Relevance
“…It is very important to improve the organizational performance of banking industry through the employee engagement and Banking sector had to improve the organisational performance through employee engagement and human resource development. Study by Hakuduwal, (2019) found significant impact on employee engagement through training and development, career development and performance management in Nepalese commercial banks. In addition Human resource practice of organizational culture, human resource training and development results positive and significant relationship with organizational citizenship behavior and employee empowerment results the negative on organizational citizenship behavior (Subedi, & Sthapit, 2020…”
Section: Statement Of Problemmentioning
confidence: 99%
“…It is very important to improve the organizational performance of banking industry through the employee engagement and Banking sector had to improve the organisational performance through employee engagement and human resource development. Study by Hakuduwal, (2019) found significant impact on employee engagement through training and development, career development and performance management in Nepalese commercial banks. In addition Human resource practice of organizational culture, human resource training and development results positive and significant relationship with organizational citizenship behavior and employee empowerment results the negative on organizational citizenship behavior (Subedi, & Sthapit, 2020…”
Section: Statement Of Problemmentioning
confidence: 99%
“…Human resource development is an organization's deliberate effort to assist staff people in acquiring behaviors, skills, knowledge, and attitudes pertinent to their professions (Hakuduwal 2019). Human resource development is a continuous process that is crucial for firms to improve company productivity and employee performance (Baniya 2006).…”
Section: Introductionmentioning
confidence: 99%
“…All motivated employees participate in and express themselves physically, mentally, and emotionally while performing their roles in organizational activities (Ahmad 1990). Every engaged employee has a positive connection with work related activities and endeavors of an organization (Niraula 2022).Employee engagement consists of three elements. The first is vigor, or performing with a lot of energy and persistence.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations